A full-fledged micromagnetic code in fewer than 70 lines of NumPy - Abert, Claas; Bruckner, Florian; Vogler, Christoph; Windl, Roman; Thanhoffer, Raphael; Suess, Dieter (Journal of magnetism and magnetic materials, 2015)
We present a complete micromagnetic finite-difference code in fewer than 70 lines of Python. The code makes a large use of the NumPy library and computes the exchange field by finite differences and the demagnetization field with a fast convolution algorithm. Since the magnetization in finite-difference micromagnetics is represented by a multi-dimensional array and the NumPy library features a rich interface for this data structure, the code we present is an ideal starting point for the development of novel algorithms. •A very concise but complete micromagnetic code written in Python is presented.•An introduction to finite-difference micromagnetics is provided.•The code is a perfect starting point for the development of novel algorithms.